The Role of Systemic Inflammation in Cancer‐Associated Muscle Wasting and Rationale for Exercise as a Therapeutic Intervention. Issue 2 (1st July 2018) - Cole, Calvin L.; Kleckner, Ian R.; Jatoi, Aminah; Schwarz, Edward M.; Dunne, Richard F.
Abstract: Progressive skeletal muscle wasting in cancer cachexia involves a process of dysregulated protein synthesis and breakdown. This catabolism may be the result of mal‐nutrition, and an upregulation of both pro‐inflammatory cytokines and the ubiquitin proteasome pathway (UPP), which can subsequently increase myostatin and activin A release. The skeletal muscle wasting associated with cancer cachexia is clinically significant, it can contribute to treatment toxicity or the premature discontinuation of treatments resulting in increases in morbidity and mortality. Thus, there is a need for further investigation into the pathophysiology of muscle wasting in cancer cachexia to develop effective prophylactic and therapeutic interventions. Several studies have identified a central role for chronic‐systemic inflammation in initiating and perpetuating muscle wasting in patients with cancer. Interestingly, while exercise has shown efficacy in improving muscle quality, only recently have investigators begun to assess the impact that exercise has on chronic‐systemic inflammation. To put this new information into context with established paradigms, here we review several biological pathways (e.g. dysfunctional inflammatory response, hypothalamus pituitary adrenal axis, and increased myostatin/activin A activity) that may be responsible for the muscle wasting in patients with cancer. Additionally, we discuss the potential impact that exercise has on these pathways in the treatment of cancer‐related muscle wasting. Exercise is an attractive intervention for muscle wasting in this population, partially because it disrupts chronic‐systemic inflammation mediated catabolism. Most importantly, exercise is a potent stimulator of muscle synthesis, and therefore this therapy may reverse muscle damage caused by cancer cachexia.